Dual Immaculate Quasisymmetric Functions Expand Positively into Young Quasisymmetric Schur Functions - Allen, Edward; Hallam, Joshua; Mason, Sarah (Discrete mathematics and theoretical computer science, 2020)
We describe a combinatorial formula for the coefficients when the dual immaculate quasisymmetric func- tions are decomposed into Young quasisymmetric Schur functions. We prove this using an analogue of Schensted insertion. We also provide a Remmel-Whitney style rule to generate these coefficients algorithmically.